2018
DOI: 10.29136/mediterranean.451553
|View full text |Cite
|
Sign up to set email alerts
|

Morphological traits of some vetch (Vicia sp.) species collected from natural flora

Abstract: Çalışma, Antalya doğal florasında bulunan adi fiğ (Vicia sativa L.), tüylü fiğ (Vicia villosa Roth.) ve koca fiğ (Vicia narbonensis L.) türlerinden tohum örnekleri toplayıp, morfolojik özelliklerini belirlemek amacıyla planlanmıştır. Araştırma, Batı Akdeniz Tarımsal Araştırma Enstitüsünde 2008-2013 yılları arasında yürütülmüştür. Türlerin bulunduğu yerlerin GPS değerleri belirlenmiştir. Toplamda gidilen 63 lokasyondan 41 adi fiğ, 15 tüylü fiğ ve 7 koca fiğ populasyonu toplanmıştır. Tüm türlerde tohum çoğaltma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The identification of suitable C4 plants that can remain green during the summer months and the development of genotypes with high yield and high forage quality among them can be effective in mitigating the severity of this problem. As a matter of fact, studies conducted by [21][22][23] reported wide variation in terms of quality within the plant materials collected from natural flora. The study of Bituminaria bituminosa (L.) C.H.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of suitable C4 plants that can remain green during the summer months and the development of genotypes with high yield and high forage quality among them can be effective in mitigating the severity of this problem. As a matter of fact, studies conducted by [21][22][23] reported wide variation in terms of quality within the plant materials collected from natural flora. The study of Bituminaria bituminosa (L.) C.H.…”
Section: Introductionmentioning
confidence: 99%